PVA optical film and preparation method thereof
By introducing humidifier processing into the preparation process of PVA optical film, the film moisture content is accurately controlled, and the problem of low stretching ratio of PVA optical film in the prior art is solved, and the stretching ratio is increased by more than 600%, which is suitable for large-scale promotion.
Patent Information
- Application Number
- CN202411927223.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-18
AI Technical Summary
The stretching ratio of the existing PVA optical film is low, making it difficult to easily control the film moisture content to improve the tensile performance.
By adding a humidifier processing between the heat treatment and winding process, the humidity, temperature and time the film passes through the humidifier are adjusted, and the film moisture content is accurately controlled, thereby improving the tensile performance of the PVA optical film.
The stretching ratio of PVA optical film has been significantly improved, with a stretching ratio of more than 600%, breaking the 550% limit of domestic existing technology. At the same time, the method is simple, low cost and suitable for large-scale promotion.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of PVA optical films, and in particular to a PVA optical film and a preparation method thereof. Background Art
[0002] The basic structure of a polarizer consists of two sides of triacetyl cellulose film (TAC) sandwiched between a layer of PVA optical film that can produce polarized light. New display technologies represented by LCD and OLED made of polarizers occupy an extremely important position in the fields of people's livelihood, high technology, and military defense.
[0003] The two most important indicators of PVA optical film are optical properties and mechanical properties, among which mechanical properties are mainly tensile properties. The higher the stretching ratio, the stronger the orientation of the polymer material constituting the film, and the better the polarization performance of the polarizer. However, at present, domestic PVA optical film can only produce products with a stretching ratio close to 550%, so it is of great significance to find a simple method to improve the tensile properties of the film.
[0004] There are many factors that affect the tensile properties of polyvinyl alcohol optical films, such as the molecular weight, molecular structure, type of plasticizer, solution formula, processing technology, etc. of polyvinyl alcohol. It is easier to improve the tensile properties of the film by changing the processing technology. The moisture content of the film has a great influence on the tensile properties. If the moisture content is too high, the tensile strength and stretch ratio of the film are low; if the moisture content is too low, the film is hard and has high tensile strength but is easy to break. Therefore, finding a way to easily control the moisture content of the film is of great significance to the tensile properties of the film. Summary of the invention
[0005] The object of the present invention is to provide a PVA optical film and a preparation method thereof, so as to solve the following technical problems:
[0006] How to easily control the moisture content of the film?
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A method for preparing a PVA optical film, characterized in that it comprises the following steps:
[0009] S1. Dissolve the PVA resin and auxiliary materials to prepare a casting solution with a mass fraction of 25%-30%;
[0010] S2. After the casting liquid is degassed by an extruder, it is cast through a die head and a casting roller, and then dried, heat treated, humidified, and finally rolled up to form a PVA optical film.
[0011] Furthermore, in step S1, the casting solution is prepared by dissolving 100 parts of PVA resin and 0.25 parts of auxiliary materials in ultrapure water and stirring them evenly to form the casting solution.
[0012] Furthermore, the PVA resin has a degree of polymerization of 2400-2800 and a degree of alcoholysis > 99%.
[0013] Furthermore, the auxiliary material includes glycerol and a surfactant in a mass ratio of 3:2.
[0014] Furthermore, the surfactant is any one of polyoxyethylene lauryl ether sulfate and lauric acid diethanolamide or a mixture of the two in any proportion.
[0015] Further, in step S2, the temperature of the heat treatment is 90-140°C;
[0016] Preferably, the heat treatment temperature is 120°C.
[0017] Further, in step S2, the humidifier treatment method is: suspending the heat-treated PVA film through a constant temperature and humidity humidifier with an internal temperature of 35-60°C and a humidity of 50-70%RH for a time of 10-25s;
[0018] Preferably, the internal temperature of the constant temperature and humidity humidifier is 50°C and the humidity is 60% RH;
[0019] Preferably, the time for the heat-treated PVA film to pass through the constant temperature and humidity humidifier is 20 seconds.
[0020] Furthermore, the constant temperature and humidity humidifier includes a closed box, and a film inlet and a film outlet are arranged on the surface of the closed box to allow the PVA film to be suspended in and out; a humidifying device is arranged inside the closed box, and the humidifying device includes a heating element and a diffusion device. The humidification method of the humidifying device is: using a heating element to generate water vapor, and the water vapor enters the closed box through the diffusion device to maintain uniform humidity in the closed box.
[0021] Furthermore, the constant temperature and humidity heater is controlled by a closed-loop control system consisting of a temperature sensor, a humidity sensor, a controller and a humidifying device.
[0022] In a second aspect, the present invention further discloses a PVA optical film, which is prepared by the method for preparing the PVA optical film as described above.
[0023] Beneficial effects of the present invention:
[0024] The present invention adds a humidifier treatment process between the heat treatment and the winding process, and then adjusts the humidity and temperature in the humidifier, and the time the film passes through the humidifier. This can accurately control the moisture content of the film, thereby improving the tensile properties of the PVA optical film. The stretching ratio exceeds 600%, breaking the current situation where the stretching ratio of PVA optical films produced domestically is close to 550%. The method is simple, easy to operate, low in cost, and effective, and is suitable for large-scale promotion and use. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.
[0027] Example 1
[0028] In parts by weight, 100 parts of PVA resin (polymerization degree 2500, alcoholysis degree 99.5%), 0.15 parts of glycerol, and 0.1 parts of a mixture of polyoxyethylene lauryl ether sulfate and lauric acid diethanolamide were dissolved in ultrapure water to prepare a casting solution with a concentration of 28%. The casting solution was degassed by an extruder, cast by a die and a roller, dried by a drying roller, and heat-treated in an oven at 120°C. Then, it entered a constant temperature and humidity humidifier at a temperature of 50°C and a humidity of 60%RH to adjust the moisture content of the film for 20 seconds, and finally rolled up to obtain a PVA optical film with a thickness of 60um.
[0029] Example 2
[0030] In parts by weight, 100 parts of PVA resin (polymerization degree 2500, alcoholysis degree 99.5%), 0.15 parts of glycerol, and 0.1 parts of a mixture of polyoxyethylene lauryl ether sulfate and lauric acid diethanolamide were dissolved in ultrapure water to prepare a casting solution with a concentration of 25%. The casting solution was degassed by an extruder, cast by a die and a roller, dried by a drying roller, and heat-treated in an oven at 140°C. Then, it entered a constant temperature and humidity humidifier at a temperature of 35°C and a humidity of 70% RH to adjust the moisture content of the film for 10 seconds, and finally rolled up to obtain a PVA optical film with a thickness of 60um.
[0031] Example 3
[0032] In parts by weight, 100 parts of PVA resin (polymerization degree 2500, alcoholysis degree 99.5%), 0.15 parts of glycerol, and 0.1 parts of a mixture of polyoxyethylene lauryl ether sulfate and lauric acid diethanolamide were dissolved in ultrapure water to prepare a casting solution with a concentration of 30%. The casting solution was degassed by an extruder, cast by a die and a roller, dried by a drying roller, and heat-treated in an oven at 140°C. Then, it entered a constant temperature and humidity humidifier at a temperature of 60°C and a humidity of 50%RH to adjust the moisture content of the film for 25s, and finally rolled up to obtain a PVA optical film with a thickness of 60um.
[0033] Example 4
[0034] In parts by weight, 100 parts of PVA resin (polymerization degree 2500, alcoholysis degree 99.5%), 0.15 parts of glycerol, and 0.1 parts of a mixture of polyoxyethylene lauryl ether sulfate and lauric acid diethanolamide were dissolved in ultrapure water to prepare a casting solution with a concentration of 28%. The casting solution was degassed by an extruder, cast by a die and a roller, dried by a drying roller, and heat-treated in an oven at 90°C. Then, it entered a constant temperature and humidity humidifier at a temperature of 50°C and a humidity of 60%RH to adjust the moisture content of the film for 20 seconds, and finally rolled up to obtain a PVA optical film with a thickness of 60um.
[0035] Example 5
[0036] In parts by weight, 100 parts of PVA resin (polymerization degree 2500, alcoholysis degree 99.5%), 0.15 parts of glycerol, and 0.1 parts of a mixture of polyoxyethylene lauryl ether sulfate and lauric acid diethanolamide were dissolved in ultrapure water to prepare a casting solution with a concentration of 28%. The casting solution was degassed by an extruder, cast by a die and a roller, dried by a drying roller, and heat-treated in an oven at 140°C. Then, it entered a constant temperature and humidity humidifier at a temperature of 50°C and a humidity of 60%RH to adjust the moisture content of the film for 20s, and finally rolled up to obtain a PVA optical film with a thickness of 60um.
[0037] Example 6
[0038] In parts by weight, 100 parts of PVA resin (polymerization degree 2500, alcoholysis degree 99.5%), 0.15 parts of glycerol, and 0.1 parts of a mixture of polyoxyethylene lauryl ether sulfate and lauric acid diethanolamide were dissolved in ultrapure water to prepare a casting solution with a concentration of 28%. The casting solution was degassed by an extruder, cast by a die and a roller, dried by a drying roller, and heat-treated in an oven at 120°C. Then, it entered a constant temperature and humidity humidifier at a temperature of 35°C and a humidity of 60%RH to adjust the moisture content of the film for 20 seconds, and finally rolled up to obtain a PVA optical film with a thickness of 60um.
[0039] Example 7
[0040] In parts by weight, 100 parts of PVA resin (polymerization degree 2500, alcoholysis degree 99.5%), 0.15 parts of glycerol, and 0.1 parts of a mixture of polyoxyethylene lauryl ether sulfate and lauric acid diethanolamide were dissolved in ultrapure water to prepare a casting solution with a concentration of 28%. The casting solution was degassed by an extruder, cast by a die and a roller, dried by a drying roller, and heat-treated in an oven at 120°C. Then, it entered a constant temperature and humidity humidifier at a temperature of 60°C and a humidity of 60%RH to adjust the moisture content of the film for 20s, and finally rolled up to obtain a PVA optical film with a thickness of 60um.
[0041] Example 8
[0042] In parts by weight, 100 parts of PVA resin (polymerization degree 2500, alcoholysis degree 99.5%), 0.15 parts of glycerol, and 0.1 parts of a mixture of polyoxyethylene lauryl ether sulfate and lauric acid diethanolamide were dissolved in ultrapure water to prepare a casting solution with a concentration of 28%. The casting solution was degassed by an extruder, cast by a die and a roller, dried by a drying roller, and heat-treated in an oven at 120°C. Then, it entered a constant temperature and humidity humidifier at a temperature of 50°C and a humidity of 50%RH to adjust the moisture content of the film for 20 seconds, and finally rolled up to obtain a PVA optical film with a thickness of 60um.
[0043] Example 9
[0044] In parts by weight, 100 parts of PVA resin (polymerization degree 2500, alcoholysis degree 99.5%), 0.15 parts of glycerol, and 0.1 parts of a mixture of polyoxyethylene lauryl ether sulfate and lauric acid diethanolamide were dissolved in ultrapure water to prepare a casting solution with a concentration of 28%. The casting solution was degassed by an extruder, cast by a die and a roller, dried by a drying roller, and heat-treated in an oven at 120°C. Then, it entered a constant temperature and humidity humidifier at a temperature of 50°C and a humidity of 70% RH to adjust the moisture content of the film for 20 seconds, and finally rolled up to obtain a PVA optical film with a thickness of 60um.
[0045] Example 10
[0046] In parts by weight, 100 parts of PVA resin (polymerization degree 2500, alcoholysis degree 99.5%), 0.15 parts of glycerol, and 0.1 parts of a mixture of polyoxyethylene lauryl ether sulfate and lauric acid diethanolamide were dissolved in ultrapure water to prepare a casting solution with a concentration of 28%. The casting solution was degassed by an extruder, cast by a die and a roller, dried by a drying roller, and heat-treated in an oven at 120°C. Then, it entered a constant temperature and humidity humidifier at a temperature of 50°C and a humidity of 60% RH to adjust the moisture content of the film for 10 seconds, and finally rolled up to obtain a PVA optical film with a thickness of 60um.
[0047] Embodiment 11
[0048] In parts by weight, 100 parts of PVA resin (polymerization degree 2500, alcoholysis degree 99.5%), 0.15 parts of glycerol, and 0.1 parts of a mixture of polyoxyethylene lauryl ether sulfate and lauric acid diethanolamide were dissolved in ultrapure water to prepare a casting solution with a concentration of 28%. The casting solution was degassed by an extruder, cast by a die and a roller, dried by a drying roller, and heat-treated in an oven at 120°C. Then, it entered a constant temperature and humidity humidifier at a temperature of 50°C and a humidity of 60% RH to adjust the moisture content of the film for 25 seconds, and finally rolled up to obtain a PVA optical film with a thickness of 60um.
[0049] Comparative Example 1
[0050] Compared with Example 1, the only difference is that the film is directly rolled up after heat treatment at 120°C in an oven without humidifier treatment. The other steps and conditions are exactly the same, and a PVA optical film with a thickness of 60 um is finally obtained.
[0051] Comparative Example 2
[0052] Compared with Example 1, the only difference is that the temperature in the constant temperature and humidity humidifier is 30° C., and the other steps and conditions remain unchanged, and finally a PVA optical film with a thickness of 60 um is obtained.
[0053] Comparative Example 3
[0054] Compared with Example 1, the only difference is that the temperature in the constant temperature and humidity humidifier is 65° C., and the other steps and conditions remain unchanged, and finally a PVA optical film with a thickness of 60 um is obtained.
[0055] Comparative Example 4
[0056] Compared with Example 1, the only difference is that the humidity in the constant temperature and humidity humidifier is 45% RH, and other steps and conditions remain unchanged, and finally a PVA optical film with a thickness of 60 um is obtained.
[0057] Comparative Example 5
[0058] Compared with Example 1, the only difference is that the humidity in the constant temperature and humidity humidifier is 75% RH, and other steps and conditions remain unchanged, and finally a PVA optical film with a thickness of 60 um is obtained.
[0059] Comparative Example 6
[0060] Compared with Example 1, the only difference is that the time in the constant temperature and humidity humidifier is 5 seconds, and the other steps and conditions remain unchanged, and finally a PVA optical film with a thickness of 60 um is obtained.
[0061] Comparative Example 7
[0062] Compared with Example 1, the only difference is that the time in the constant temperature and humidity humidifier is 30 seconds, and the other steps and conditions remain unchanged, and finally a PVA optical film with a thickness of 60 um is obtained.
[0063] The performance of the PVA optical films prepared in Examples 1-11 and Comparative Examples 1-7 was tested using the following method:
[0064] Moisture content: The measuring instrument is a Mettler-Toledo rapid moisture tester, and the halogen drying method is selected; a certain mass of PVA optical film (0.5g-1.0g) is weighed in a sample tray, the temperature is adjusted to 110°C, and the drying time is 8 minutes.
[0065] Crystallinity: Crystallinity (%) = enthalpy value / 138.6 (enthalpy value of pure PVA) × 100.
[0066] Tensile properties: Cut a piece of A4 paper-sized sample of the PVA optical film along the production line direction and perpendicular to the production line, and use a sample making machine to cut the A4 paper-sized sample into strips of 270mm in length and 15mm in width, and then test the transverse and longitudinal tensile strength and stretching ratio on a single-column tensile testing machine.
[0067] The test results are listed in Table 1. Table 1 is as follows:
[0068] Table 1
[0069]
[0070] By analyzing the data in Table 1, it can be known that, compared with Comparative Examples 1-7, the PVA optical films prepared in Examples 1-11 have a more moderate moisture content, and both the tensile strength and the stretch ratio are at a higher level.
[0071] Specifically, compared with Example 1, Comparative Example 1 was not treated with a humidifier, and the moisture content was significantly lower; compared with Example 1, Comparative Example 3 had a humidifier temperature that was too high, and the moisture content was significantly lower; compared with Example 1, Comparative Example 4 had a humidifier humidity that was too low, and the moisture content was significantly lower; compared with Example 1, Comparative Example 6 had a humidifier time that was too short, and the moisture content was significantly lower; therefore, the PVA optical films obtained in Comparative Examples 1, 3, 4, and 6 had too low moisture content, so although their tensile strength was relatively high, they were easily broken during the stretching process, and the stretching ratio was low.
[0072] Compared with Example 1, the temperature of Comparative Example 2 passing through the humidifier is too low, and the moisture content is significantly higher; compared with Example 1, the humidity of Comparative Example 5 passing through the humidifier is too high, and the moisture content is significantly higher; compared with Example 1, the time of passing through the humidifier in Comparative Example 7 is too high, and the moisture content is significantly higher; therefore, the PVA optical films obtained in Comparative Examples 2, 5, and 7 have lower tensile strength and stretching ratio due to their too high moisture content.
[0073] To sum up, under the premise of maintaining a high heat treatment setting temperature (that is, the crystallinity of the film is high), controlling the temperature and humidity of the humidifier and the time the film passes through the humidifier can well control the moisture content of the optical film, and its tensile strength and stretching ratio are also good. The stretching ratio exceeds 600%, breaking the current situation of the domestic production of PVA optical film with a stretching ratio of nearly 550%.
[0074] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for preparing a PVA optical film, characterized in that: The steps include: S1. Dissolve the PVA resin and auxiliary materials to prepare a casting solution with a mass fraction of 25%-30%; S2. After the casting liquid is degassed by an extruder, it is cast through a die head and a casting roller, and then dried, heat treated, humidified, and finally rolled up to form a PVA optical film.
2. The method for preparing a PVA optical film according to claim 1, characterized in that: In step S1, the casting solution is prepared by dissolving 100 parts of PVA resin and 0.25 parts of auxiliary materials in ultrapure water and stirring them evenly to form the casting solution.
3. The method for preparing a PVA optical film according to claim 2, characterized in that: The PVA resin has a polymerization degree of 2400-2800 and an alcoholysis degree of more than 99%.
4. The method for preparing a PVA optical film according to claim 2, characterized in that: The auxiliary materials include glycerol and a surfactant in a mass ratio of 3:
2.
5. The method for preparing a PVA optical film according to claim 4, characterized in that: The surfactant is any one of polyoxyethylene lauryl ether sulfate and lauric acid diethanolamide or a mixture of the two in any proportion.
6. The method for preparing a PVA optical film according to claim 1, characterized in that: In step S2, the temperature of the heat treatment is 90-140°C.
7. The method for preparing a PVA optical film according to claim 1, characterized in that: In step S2, the humidifier treatment method is: suspending the heat-treated PVA film through a constant temperature and humidity humidifier with an internal temperature of 35-60°C and a humidity of 50-70%RH for a time of 10-25s.
8. The method for preparing a PVA optical film according to claim 7, characterized in that: The constant temperature and humidity humidifier includes a closed box, and a film inlet and a film outlet are arranged on the surface of the closed box to allow the PVA film to float in and out; a humidifying device is arranged inside the closed box, and the humidifying device includes a heating element and a diffusion device. The humidification method of the humidifying device is: using a heating element to generate water vapor, and the water vapor enters the closed box through the diffusion device to maintain uniform humidity in the closed box.
9. The method for preparing a PVA optical film according to claim 8, characterized in that: The constant temperature and humidity heater is controlled by a closed-loop control system consisting of a temperature sensor, a humidity sensor, a controller and a humidifying device.
10. A PVA optical film, characterized in that: The PVA optical film is prepared by the method for preparing a PVA optical film according to any one of claims 1 to 9.